Peningkatan Literasi Keuangan Menuju Masyarakat Mandiri Financial - Devi Lestari Paramita Putri; Rohmaniyah Rohmaniyah; Nurul Alfian; Subhan Subhan; Achmarul Fajar; Zef Risal (Universitas Maritim AMNI Semarang, 2025)
Financial literacy can increase insight in making wise and effective decisions related to financial planning in the future. Improving financial literacy is an urgent need in building an economically strong, independent, and stable society. Effective financial literacy education and programs can help individuals understand and manage their finances better, as well as improve overall financial well-being. The purpose of this community service is to provide education and understanding about financial management to achieve financial independence. The method of this service is by educating and mentoring the PKK group in Ceguk village regarding financial literacy. Through comprehensive counseling and training, participants gain the knowledge and skills needed to manage personal and family finances more wisely. Financial literacy can increase insight in making wise and effective decisions related to financial planning in the future.